Scleraspis nom. nov., replacement name for Pycnaspis Van Syoc & Dekelboum, 2011 - van Syoc, Robert J.; Dekelboum, Allen M. (Zootaxa, 2012)
In the recently published revision of the barnacle family Oxynaspididae (Van Syoc & Dekelboum 2011), the genus name Pycnaspis was proposed for oxynaspidids with the following characteristics: scutum with shallow adductor muscle pit, lacking distinct ridge running from umbo to apex; tergum proximal to scutum and carina, without prominent projections on margins or raised bumps on surface; carina with surface smooth, basal end rounded, not forked.